Cold on-column injection coupled with gas chromatography/mass spectrometry for determining halonitromethanes in drinking water. Issue 2 (9th December 2015) - Chen, Haifeng; Yin, Jinbao; Zhu, Mengjie; Cao, Cong; Gong, Tingting; Xian, Qiming
Abstract : Halonitromethanes (HNMs) are a class of halogenated nitrogenous disinfection by-products (N-DBPs) in drinking water which possess health concerns due to their potentially higher toxicity than regulated disinfection by-products (DBPs). Abstract : Halonitromethanes (HNMs) are a class of halogenated nitrogenous disinfection by-products (N-DBPs) in drinking water which possess health concerns due to their potentially higher toxicity than regulated disinfection by-products (DBPs). A cold on-column (COC) injection in track-oven mode coupled with a gas chromatography-mass spectrometry (GC-MS) system for the analysis of HNMs has been developed. Comparative experiments showed that COC had an advantage over the conventional split/splitless injection in minimizing thermal degradation of HNMs, especially dibromochloro- and tribromo-nitromethanes in water. Both debromo- and denitro-products of HNMs were observed in the splitless injection mode at 117 °C and 170 °C. Liquid–liquid extraction (LLE) and solid phase extraction (SPE) procedures were compared for sample pretreatment. LLE showed good recoveries of 73–91% for all nine HNMs. In comparison, SPE provided a similar recovery range for four commonly detected HNMs in drinking water: dichloronitromethane, trichloronitromethane, bromochloronitromethane and dibromonitromethane in drinking water, while the recoveries of the other HNMs were below 50%. This indicated that the SPE-COC-GC-MS method can be a good alternative to LLE-COC-GC-MS for the identification and quantification of the four HNMs commonly present in tap water due to the simplicity of the SPE pretreatment technique.